In House Training Penelusuran Informasi Berbasis Literasi Digital Dalam Penulisan Artikel Ilmiah Guru SMPN Kota Padang - Farel Olva Zuve; Atmazaki Atmazaki; Ardoni Ardoni; Amril Amir; Afnita Afnita; Ridha Hasnul Ulya; Mita Domi Fella Henanggil (Jurnal Pengabdian UNDIKMA, 2023)
This service activity aims to improve teacher writing skills and the ability to search for reliable information as a source of reference and create digital libraries for writing scientific articles. The method of implementing this service used training. This service partner was the teachers at SMPN 16 Padang. The instruments for evaluating this service activity were the articles written by the teachers, which were analyzed descriptively. The results of this service showed that teachers could produce relevant scientific articles that could be used for teacher promotion. Approximately 80% of teachers could master how to turn class action research reports into scientific articles. In addition, this activity could improve 100% of teachers' understanding of the procedures for writing and publishing scientific articles in accredited journals. This success was seen from the articles made by the teachers according to the template from the specified journal.Â Â